STUDI FENOMENOLOGI DAMPAK DISMINOREA PADA POLA KEBIASAAN REMAJA DI SMP NEGERI I RAMBAH KECAMATAN RAMBAH KABUPATEN ROKAN HULU PROPINSI RIAU - Apridayati, Rita; Wahyuni Tami Lubis, (Maternity and Neonatal : Jurnal Kebidanan, 2023)
Dysminorrhoea is a menstrual disorder in which a medical condition occurs during menstruation/menstruation that can affect or interfere with activities, symptoms that are often experienced include pain or soreness in the abdominal or pelvic area. According to the WHO (2015), 264 million people feel anxiety. Anxiety includes fear, fatigue, insomnia, and digestive problems. Based on the World Health Organization, 50% of women in every country suffer from dysminorrhea dysminorrhea. Based on data from Rokan Hulu Health Service, it is known that the prevalence of anxiety reaches 4.3% (4,936 people) felt anxiety, and 59.5% of teenagers had dysminorrhea. Therefore, this study aims to determine Teenagers’ Anxiety Toward Dysminorrhea at SMP Negeri I Rambah, Rambah, Rokan Hulu, Riau. It was qualitative research with a descriptive phenomenological approach. It was conducted on May-June 2020 at SMP Negeri I Rambah, Rambah, Rokan Hulu, Riau. The data was collected through in-depth interviews. By using purposive sampling technique, 7 participants were chosen as the samples. at SMP Negeri I Rambah, Rambah, Rokan Hulu, Riau The results of this study found in 3 themes 1. Characteristics of pain adolescents 2 The Impact of Dysminorea. 3 Efforts to deal with dysminorea by participants. The conclusion of this study, the characteristics of dysminorrhea, efforts and impact of dysminorrhea to prevent anxiety in adolescent dysminorrhea. Therefore, it is hoped that health workers can increase health promotion activities to prevent anxiety for teenagers who suffer from dysminorrhea.